Sequelae of Hospitalization for Diabetic Foot Ulcers at LASUTH Ikeja Lagos: A Prospective Observational Study - Adeleye, Olufunmilayo Olubusola; Williams, Adetutu Oluwatosin; Dada, Akin Olusola; Ugwu, Ejiofor T.; Ogbera, Anthonia Okeoghene; Sodipo, Olujimi Olanrewaju (Frontiers in Clinical Diabetes and Healthcare, 2022)
Abstract Diabetic foot ulcers (DFUs) remain important sequelae of diabetes (DM) which cause debilitating effects on the sufferer. The evolution of some aspects of epidemiology and the current clinical impact of DFUs was examined. Methods A single-center prospective observational study. Study subjects were consecutively recruited. Results Total medical admissions during the study period were 2288, 350 were DM related, out of these 112 were admitted for DFU. 32% of total DM admissions were for DFU. The mean age of the study subjects is 58 ± 11.0 range is from 35 years to 87 years. Males were slightly predominant (51.8%). Most of them were actively employed (92%), and the majority were in the 55 to 64 years age category. Most of them had not been diabetic for longer than 8 years (61%). The mean duration of DM is 8.32±7.27 years. The mean duration of ulcer at presentation was 72.0±138.13 days. The majority of the patients (80.3%) presented with severe (grades 3 to 5) ulcers, Wagner grade four was the most predominant. Regarding clinical outcome, 24 (24.7%) had an amputation, 3 of which were minor. The factor that was associated with amputation was concomitant heart failure – OR 6.00 CI 0.589-61.07, 0.498-4.856. Death occurred in 16 (18.4%). The factors associated with mortality were severe anemia OR 2.00 CI 0.65 – 6.113, severe renal impairment requiring dialysis OR 3.93 CI 0.232-66.5, concomitant stroke OR 8.42 CI 0.71-99.6, and peripheral arterial disease- OR 18.33 CI 2.27 -147 p-value- 0.006. Conclusion The hallmark of DFU in this report is late presentation, it accounted for a significant proportion of the total medical admissions, although the case fatality of DFU reduced from previous reports from the center, mortality, and amputation rates are still unacceptably high. Concomittant heart failure was a factor of amputation. Mortality was associated with severe anemia, renal impairment and peripheral arterial disease.